A Fibre Optic Long Period Grating Immunosensor for Campylobacter jejuni with Enhanced Sensitivity by Bacterial Staining - Rendon Romero, Antonio (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018. Campylobacteriosis is one of the most widely reported bacterial cause of gastroenteritis in humans in the world. One of the bacterial species that most causes the disease is Campylobacter jejuni. The detection of Campylobacter jejuni by sensitising the surface of an optical fibre long period grating (LPG) with covalently attached rabbit polyclonal antibody is explored. The sensitivity of the sensor is enhanced by bacterial staining allowing the detection of concentration as low as 102CFU/mL. Finally, the selectivity of the sensor against other bacterial species is evaluated.
Keywords: long period grating'; 'bacterial'; 'immunosensor'; 'CranfieldDN2018'; 'Biotechnology'